2022
DOI: 10.1182/blood.2021013290
|View full text |Cite
|
Sign up to set email alerts
|

Blinatumomab maintenance after allogeneic hematopoietic cell transplantation for B-lineage acute lymphoblastic leukemia

Abstract: Patients with B-lineage acute lymphoblastic leukemia (ALL) are at high-risk for relapse after allogeneic hematopoietic cell transplantation (HCT). We conducted a single center phase II study evaluating the feasibility of 4 cycles of blinatumomab administered every 3 months during the first year after HCT in an effort to mitigate relapse in high-risk ALL patients. Twenty-one of 23 enrolled patients received at least one cycle of blinatumomab and were included in the analysis. The median time from HCT to the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 41 publications
3
35
0
1
Order By: Relevance
“…To note, a recent phase 2 study demonstrated the feasibility and safety of post allo-HSCT blinatumomab based maintenance in 21 patients including 2 Ph+ ALL patients [ 116 ]. Several prospective trials are ongoing to clarify the implementation of post-allo HSCT maintenance ( Table 2 ).…”
Section: Allogeneic Hematopoietic Stem Cellmentioning
confidence: 99%
“…To note, a recent phase 2 study demonstrated the feasibility and safety of post allo-HSCT blinatumomab based maintenance in 21 patients including 2 Ph+ ALL patients [ 116 ]. Several prospective trials are ongoing to clarify the implementation of post-allo HSCT maintenance ( Table 2 ).…”
Section: Allogeneic Hematopoietic Stem Cellmentioning
confidence: 99%
“…Therefore, blinatumomab gained accelerated approval by FDA to treat BCP ALL with MRD greater than or equal to 0.1% after the first or second CR. Moreover, a phase II study (NCT02807883) has proved the feasibility of blinatumomab maintenance following alloHSCT for patients with B-cell ALL at high-risk for relapse, with the 1-year overall survival (OS), progression-free survival (PFS), and nonrelapse mortality (NRM) rates of 85%, 71%, and 0%, respectively ( 30 ). In addition, to incorporate blinatumomab as part of upfront treatment for pediatric B-cell ALL, several trials are currently ongoing (NCT03643276 and NCT03914625) ( 31 ).…”
Section: T Cell-based Immunotherapymentioning
confidence: 99%
“…In the future, screening tumor markers to predict CD19-negative relapse should be paid more attention. What’s more, overexpression of checkpoint molecules including T-cell immunoglobulin and mucin domain 3 (TIM-3) on T cells and PD-L1 on tumor cells represented an additional potential escape mechanism from immunosurveillance ( 30 , 59 , 60 ). Adding immune checkpoint inhibitors to blinatumomab treatment thus overcoming resistance may be feasible ( 60 ) and are under clinical investigation (NCT03160079, NCT03512405 and NCT04546399).…”
Section: T Cell-based Immunotherapymentioning
confidence: 99%
“…93 The use of posttransplant maintenance strategies has been explored in ALL; post-HSCT TKI maintenance in adults with Ph1 ALL has been shown to reduce relapse and is generally recommended, 94,95 whereas post-HSCT maintenance approaches in PhÀ ALL are currently limited to early investigations. 96 The importance of MRD clearance before HSCT has been established and is now achievable in B-ALL after blinatumomab, 73 and post-HSCT MRD monitoring of the bone marrow or peripheral blood using sensitive next-generation sequencing-based technologies has been incorporated into clinical practice. 97 Finally, novel HSCT graft engineering approaches are offering the promise of reduced graft-versus-host disease with preserved or improved efficacy 98,99 and are now being tested in confirmatory clinical trials (NCT04013685).…”
Section: Allogeneic Hsct In Adult Allmentioning
confidence: 99%